Work Discipline on the Performance of UMKM Inboxmie Employees - Yulia Nur Fadilah; Dhea Amelia Putri; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The method used to collect data is descriptive method with observation and interviews. Based on the results of interviews with MSME owners, it was found that there were problems with the discipline of the employees who worked. The discipline problem that occurs in this Inboxmie business is the lack of time discipline for its employees, namely they are often late to work hours, and do not come to work without clear explanations. This of course violates the provisions set by the MSME business owner. Problems that occur can cause non-optimal business. Some efforts that need to be made to overcome the problem of work discipline on employee performance is by providing an orientation program for employees. The author concludes that the problem faced by these SMEs is the lack of discipline in employees. One of the factors that can increase productivity is work discipline.